ASSESSMENT OF MISTAKES OF AN OPERATOR AT QUANTITATIVE ANALYSIS OF STRUCTURE BY COMPU- TER METHODS - A. G. Anisovich; A. V. Basalaj (Литьë и металлургия)
Mistakes of an operator at quantitative analysis of microstructure at working in the program of images processing Image SP are considered. The mistake arising at the stage of creation of the calibration table of increases is defined.